The Effect of Logistical-Crossfunctional Drivers on the Competitive Strategy of the Supply Chain of SMEs: A Case Study - Sumarsono sumarsono; Nur Muflihah (Jurnal Teknik Industri, 2021)
Small and Medium Enterprises (SMEs) dominate the business world in Indonesia with a high Gross Domestic Product contribution. However, SMEs are unable to compete with large industries due to uncompetitive supply chains. The logistical-crossfunctional aspect of drivers is an aspect driving a competitive supply chain. This study aims to examine the effect of logistical-crossfunctional drivers on the competitive strategy of the supply chain for SMEs in Indonesia. The case study was conducted in SMEs scattered in East Java, Indonesia. The data analysis method used PLS-SEM. The results showed that the logistical-crossfunctional aspects of SME drivers have a significant effect on the supply chain competitive strategy. The implications of the research results are used to develop supply chain strategies for SMEs with a priority scale of logistical-crossfunctional drivers such as 1) facilities; 2) sourcing; 3) information; 4) transportation; 5) inventory; and 6) pricing.